Drying Characteristics of Cacao Beans using Modified Solar Tunnel Dryer Type Hohenheim - Khathir*, Rita; Kurniawan, Edi; Yunita, Yunita; Syafriandi, Syafriandi (Graduate School of Universitas Syiah Kuala, 2023)
Drying cacao has been conducted by open-sun drying systems by farmers worldwide. To improve the cacao drying, the use of solar dryers can be applied. The objective of this study was to evaluate the drying characteristics of using a modified solar tunnel dryer type Hohenheim in drying cacao. As a comparison, the sun-drying method was also conducted. The parameters observed were temperature, relative humidity (RH), weight loss, moisture content, fat content, hardness, and drying rate. Results showed that the average temperature of the Hohenheim dryer was higher at about 10C than the ambient temperature. However, the Hohenheim dryer's drying temperature fluctuated due to the oscillation of solar irradiation. The drying process took time for 12h in 2 days. The humidity in the drying chamber was high, above 50%, representing that the dryer needed additional fans to improve its air circulation. The final moisture content of cacao dried using Hohenheim dryer and sun-drying was 12.7 and 17.4%, respectively. The drying rate of cacao dried using a Hohenheim dryer was double that of sun-drying. Therefore, the dryer can speed up the drying time and protect the cacao from contamination.